Air Pollution Beyond Boundaries: Opportunities for Ecological Modernization in Paso del Norte - Santes Álvarez, Ricardo (Frontera Norte, 2017)
Air pollution in Paso del Norte, the region encompassing Sunland Park, New Mexico, El Paso, Texas, and Ciudad Juárez, Chihuahua, is a contentious matter. Grassroots and nongovernmental organizations on both sides of the border have pressed the governments of Mexico and the United States to seek solutions. The La Paz Agreement and the environmental institutions that emerged with the NAFTA entail binational efforts to tackle common concerns. However, several factors have prevented reaching satisfactory outcomes. The lesson is that institutions have internalized the air problem, through "air programs," and they have not arrived at any solution. Ecological modernization is an alternative to traditional modes of addressing environmental matters. A process of ecomodernization is happening in Paso del Norte, but its success is limited. RESUMEN La contaminación del aire en Paso del Norte es un asunto preocupante. Algunos ciudadanos y organismos no gubernamentales compelen a los gobiernos de México y Estados Unidos a buscar soluciones a este problema binacional. El Acuerdo de La Paz y las instituciones que nacieron junto con el Tratado de Libre Comercio representan esfuerzos para confrontar los problemas ambientales fronterizos; sin embargo, varios factores han impedido alcanzar resultados satisfactorios. La lección es que las instituciones han internalizado el problema a través de "programas de aire" y, por consiguiente, no han arribado a su solución. La modernización ecológica es una alternativa a la gestión ambiental tradicional. En este artículo expongo que en Paso den Norte ocurre un proceso de ecomodernización. Concluyo que aunque la modernización ecológica se presenta en la región, su éxito es limitado.